Superconducting properties of yttrium, y subtitution in bscco-2223 / Muhammad Ridzwan Ramli - Ramli, Muhammad Ridzwan (Faculty Of Applied Sciences, 2017)
In this study, the Bi1.6-xYxPbo.4Sr2Ca2Cu30 δ has been made with yttrium concentration, x = 0.00, 0.02, 0.05, 0.10, 0.15, 0.20. The samples were prepared by using solid state method by mixing powders of Bh03, Y203, PbO, srCo3, CaC03 and CuO. The samples were characterized by X-ray diffraction and electrical resistivity measurement by four point probe. It was found that further addition of Yttrium decreased the critical temperature, Tc and critical current density, Jc. All the samples have Tc zero in the range of 50K to 97K. The decreasing of Tc value due to the decreasing of the hole concentration and transport properties of the samples. The Jc value was measured to be 0.947 A/cm2 for pure sample and decrease to 0.266 A/cm2 for x= 0.02 at 77K. The crystallographic structure of all the samples form in orthorhombic shape